2003
DOI: 10.1093/emboj/cdg085
|View full text |Cite
|
Sign up to set email alerts
|

Vibrio harveyi quorum sensing: a coincidence detector for two autoinducers controls gene expression

Abstract: In a process called quorum sensing, bacteria communicate with one another by exchanging chemical signals called autoinducers. In the bioluminescent marine bacterium Vibrio harveyi, two different autoinducers (AI-1 and AI-2) regulate light emission. Detection of and response to the V.harveyi autoinducers are accomplished through two two-component sensory relay systems: AI-1 is detected by the sensor LuxN and AI-2 by LuxPQ. Here we further de®ne the V.harveyi quorum-sensing regulon by identifying 10 new quorum-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
222
0

Year Published

2006
2006
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 238 publications
(230 citation statements)
references
References 41 publications
(62 reference statements)
8
222
0
Order By: Relevance
“…As brine shrimp larvae are transparent, using bioluminescence as a read-out of quorum sensing activity allowed us to perform this kind of analysis. Quorum sensing-regulated bioluminescence has been used before in many studies investigating the quorum sensing activity of Vibrio harveyi (Bassler et al, 1994;Freeman and Bassler, 1999;Surette et al, 1999;Lilley and Bassler, 2000;Mok et al, 2003;Henke and Bassler, 2004b). We found that the bacteria behave remarkably similar in different larvae, despite the fact that only half of them survive the infection.…”
Section: Introductionmentioning
confidence: 76%
See 1 more Smart Citation
“…As brine shrimp larvae are transparent, using bioluminescence as a read-out of quorum sensing activity allowed us to perform this kind of analysis. Quorum sensing-regulated bioluminescence has been used before in many studies investigating the quorum sensing activity of Vibrio harveyi (Bassler et al, 1994;Freeman and Bassler, 1999;Surette et al, 1999;Lilley and Bassler, 2000;Mok et al, 2003;Henke and Bassler, 2004b). We found that the bacteria behave remarkably similar in different larvae, despite the fact that only half of them survive the infection.…”
Section: Introductionmentioning
confidence: 76%
“…HAI-1, harveyi autoinducer-1, is 3-hydroxybutanoyl-L-homoserine lactone; AI-2, autoinducer-2, is the furanosyl borate diester 3A-methyl-5,6-dihydro-furo(2,3-D) (1,3,2)diox-aborole-2,2,6,6A-tetraol; and CAI-1, cholerae autoinducer-1, is (S)-3-hydroxytridecan-4-one. In addition to bioluminescence, Vibrio harveyi quorum sensing has been found to control the expression of different virulence genes in vitro, including a type III secretion system (Henke and Bassler, 2004a), extracellular toxin (Manefield et al, 2000), metalloprotease (Mok et al, 2003), siderophore (Lilley and Bassler, 2000), chitinase (Defoirdt et al, 2010b) and phospholipase (Natrah et al, 2011). However, scientists are becoming increasingly aware that growth in complex environments of the 'real world' (such as a host) contrasts with the standardised and idealised conditions in laboratory monocultures (Smith, 2000;Virgin, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…To coordinate such cooperative ventures, bacteria have developed methods of cell-to-cell signaling (14)(15)(16)(17)(18)(19), including direct physical interactions by extra membrane polymers (20)(21), secretion of extracellular materials like lubricating surfactin (22)(23), biochemical communication such as quorum sensing and chemotaxis signaling (by using mediators ranging from simple molecules and polymers to peptides and complex proteins) (24)(25)(26)(27)(28)(29), and exchange of genetic information (by plasmids and viruses) (30)(31)(32). Bacterial communication-based cooperation can lead to colony morphogenesis, coordinated gene expression, regulated cell differentiation, and division of tasks.…”
mentioning
confidence: 99%
“…Phenotypes that were found to be controlled by the V. harveyi quorum sensing system in vitro include bioluminescence (Bassler et al, 1993) and the production of several virulence factors such as a type III secretion system (Henke and Bassler, 2004a), extracellular toxin (Manefield et al, 2000), metalloprotease (Mok et al, 2003) and a siderophore (Lilley and Bassler, 2000). Recently, using quorum sensing mutants, we found that the AI-2-mediated channel of the V. harveyi quorum sensing system regulates virulence of the bacterium towards the brine shrimp Artemia franciscana in vivo (Defoirdt et al, 2005).…”
Section: Quorum Sensing-bacterial Cell-to-cell Communicationmentioning
confidence: 99%